D9.1 Communication Action Plan, WP9 - Papoutsa, Christiana; Themistocleous, Kyriacos; Schreier, Gunter; Kontoes, Haris; Christia, Eleni; Buhl, Johannes; Komodromos, George; Tziortzis, Stelios (My University, 2019)
This report represents the Communication Strategy and Action Plan for the project EXCELSIOR, Deliverable D9.1. The Communication Action Plan aims to produce a strategic communication roadmap for the ECoE Communication and Dissemination activities to ensure maximum visibility and awareness has been developed and reached targeted audiences. It aims to highlight the different communication target audiences, the tools, methodologies and expected impacts utilised towards their effective involvement in the project’s activities. Thus, the communication tools (e.g. website, brochure, events) and strategic communication priorities are tailored considering the diverse nature of the different stakeholder groups. The present document constitutes the first issue of ‘Communication Action Plan’ in the framework of the EXCELSIOR project, dedicated to Task 9.1 ‘Communication strategy and action plan’ under the work package WP9 ‘Communication, Engagement and Networking’. The Communication Action plan will be updated according to the needs of the communication strategy. D9.1 is delivered on Month 02 of the project and focuses on the first 15 months of the project, up to the first reporting period of the project. This document will be updated twice, one in Month 32 and one in Month 70 of the project, shared with partners in order to adopt a common policy related to any communication, branding and outreach activities implemented under the auspices of the ECoE.